Wait-and-see-ism as partial adoption of management practices: The rise and stall of integrated reporting - Endenich, Christoph; Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Strategic Organization)
Integrated reporting has widely been promoted as the next evolutionary step in corporate disclosure, which would soon replace traditional reporting practices. Embedded in a zeitgeist that favors sustainability, this outlook would suggest high integrated reporting adoption rates among reporting organizations. Our analysis of integrated reporting in Germany from 2008 to 2019 shows, however, that organizations approached integrated reporting with a wait-and-see mentality. This approach cannot be described adequately by the existing conceptualizations of (partial) practice adoption. We therefore develop the notion of wait-and-see-ism, defined as the deliberate and potentially long-lasting postponement of a decision to adopt a practice while its further development is monitored silently. We see limited, though continuous, efforts to prepare for the prospect of adopting the practice of integrated reporting quickly at a later stage. Wait-and-see-ism expands on prior work on partial adoption by emphasizing its temporal dimension. This adds an important yet undertheorized option that organizations can employ to respond to ambiguous institutional demands, thus explaining the stalling of promising management practices.
Keywords: Strategy and Management; Industrial relations; Education; Business and International Management

Since Albert and Whetten: the dissemination of Albert and Whetten’s conceptualization of organizational identity - Knorr, Karin; Hein-Pensel, Franziska (Management Review Quarterly)
Abstract Since the seminal work of Albert and Whetten, the organizational identity concept has become ubiquitous and highly relevant in various fields. This study systematically reviews how Albert and Whetten’s concept of organizational identity has been disseminated in different research areas. It employs quantitative (topic modeling) and qualitative text analysis, as well as a network analysis to examine a sample of 1,041 papers published between 1985 and mid-2022 that cite Albert and Whetten’s seminal work. Using this method of systematic literature analysis, the current study investigates the criteria of the basic definition and hypotheses mentioned in their work that contribute to its increasing significance, and those with the potential to become substantial aspects of future organizational identity research. Accordingly, Albert and Whetten’s conceptualization of organizational identity is often partially adopted in the literature. Thus, this study contributes to organizational identity research by unveiling further research questions on the evolving character of organizational identity, research methodology, and quantitative operationalization, on the basis of Albert and Whetten’s organizational identity conceptualization.
Keywords: Strategy and Management; Business; Management and Accounting (miscellaneous)

(How) do advanced data and analyses enable HR analytics success? A neo-configurational analysis - Strohmeier, Stefan; Collet, Julian; Kabst, Rüdiger (Baltic Journal of Management)
Purpose Enabled by increased (“big”) data stocks and advanced (“machine learning”) analyses, the concept of human resource analytics (HRA) is expected to systematically improve decisions in human resource management (HRM). Since so far empirical evidence on this is, however, lacking, the authors' study examines which combinations of data and analyses are employed and which combinations deliver on the promise of improved decision quality. Design/methodology/approach Theoretically, the paper employs a neo-configurational approach for founding and conceptualizing HRA. Methodically, based on a sample of German organizations, two varieties (crisp set and multi-value) of qualitative comparative analysis (QCA) are employed to identify combinations of data and analyses sufficient and necessary for HRA success. Findings The authors' study identifies existing configurations of data and analyses in HRM and uncovers which of these configurations cause improved decision quality. By evidencing that and which combinations of data and analyses conjuncturally cause decision quality, the authors' study provides a first confirmation of HRA success. Research limitations/implications Major limitations refer to the cross-sectional and national sample and the usage of subjective measures. Major implications are the suitability of neo-configurational approaches for future research on HRA, while deeper conceptualizing and researching both the characteristics and outcomes of HRA constitutes a core future task. Originality/value The authors' paper employs an innovative theoretical-methodical approach to explain and analyze conditions that conjuncturally cause decision quality therewith offering much needed empirical evidence on HRA success.
Keywords: Management of Technology and Innovation; Marketing; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management

A private sustainable partner selection model for green public-private partnerships and regional economic development - Tavana, Madjid; Khalili Nasr, Arash; Mina, Hassan; Michnik, Jerzy (Socio-Economic Planning Sciences)
Keywords: Management Science and Operations Research; Statistics; Probability and Uncertainty; Strategy and Management; Economics and Econometrics; Geography; Planning and Development

A comprehensive framework for sustainable closed-loop supply chain network design - Tavana, Madjid; Kian, Hadi; Nasr, Arash Khalili; Govindan, Kannan; Mina, Hassan (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

A technology development framework for scenario planning and futures studies using causal modeling - Tavana, Madjid; Ghasrikhouzani, Mohsen; Abtahi, Amir-Reza (Technology Analysis & Strategic Management)
Keywords: Management Science and Operations Research; Strategy and Management

A multi-distance interval-valued neutrosophic approach for social failure detection in sustainable municipal waste management - Ebadi Torkayesh, Ali; Tavana, Madjid; Santos-Arteaga, Francisco J. (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

How entrepreneur’s leadership behavior and demographics shape applicant attraction to new ventures: the role of stereotypes - Hubner-Benz, Sylvia; Rudic, Biljana; Baum, Matthias (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

From entrepreneurial experience to expertise: A self-regulated learning perspective - Winkler, Christoph; Fust, Alexander; Jenert, Tobias (Journal of Small Business Management)
Keywords: Management of Technology and Innovation; Strategy and Management; General Business; Management and Accounting

Early Disclosure of Invention and Reduced Duplication: An Empirical Test - Lück, Sonja; Balsmeier, Benjamin; Seliger, Florian; Fleming, Lee (Management Science)
Much work on innovation strategy assumes or theorizes that competition in innovation elicits duplication of research and that disclosure decreases such duplication. We validate this empirically using the American Inventors Protection Act (AIPA), three complementary identification strategies, and a new measure of blocked future patent applications. We show that AIPA—intended to reduce duplication, through default disclosure of patent applications 18 months after filing—reduced duplication in the U.S. and European patent systems. The blocking measure provides a clear and micro measure of technological competition that can be aggregated to facilitate the empirical investigation of innovation, firm strategy, and the positive and negative externalities of patenting. This paper was accepted by Joshua Gans, business strategy.
Keywords: Management Science and Operations Research; Strategy and Management